2016
DOI: 10.1371/journal.pone.0159989
|View full text |Cite
|
Sign up to set email alerts
|

The Mitochondrial Unfolded Protein Response Protects against Anoxia in Caenorhabditis elegans

Abstract: The mitochondrial unfolded protein response (UPRmt) is a surveillance pathway that defends proteostasis in the “powerhouse” of the cell. Activation of the UPRmt protects against stresses imposed by reactive oxygen species, respiratory chain deficits, and pathologic bacteria. Consistent with the UPRmt’s role in adaption, we found that either its pharmacological or genetic activation by ethidium bromide (EtBr) or RNAi of the mitochondrial AAA-protease spg-7 was sufficient to reduce death in an anoxia-based Caeno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 54 publications
2
32
0
Order By: Relevance
“…Little information about the impact of URPmt is described in the context of heart diseases. Acute ischemia/hypoxia-reperfusion induces UPRmt in C. elegans [39] or endothelial cells [40] and can be a protective response. However, loss of the mitochondrial aspartyl tRNA-synthetase encoding gene DARS2 in mice results in dysregulation of mitochondrial translation and strong cardiomyopathy associated with an increase of UPRmt markers [41].…”
Section: Mitochondrial Quality Controlmentioning
confidence: 99%
“…Little information about the impact of URPmt is described in the context of heart diseases. Acute ischemia/hypoxia-reperfusion induces UPRmt in C. elegans [39] or endothelial cells [40] and can be a protective response. However, loss of the mitochondrial aspartyl tRNA-synthetase encoding gene DARS2 in mice results in dysregulation of mitochondrial translation and strong cardiomyopathy associated with an increase of UPRmt markers [41].…”
Section: Mitochondrial Quality Controlmentioning
confidence: 99%
“…Our data demonstrate that transient loss of PMF during 84 preconditioning is necessary and sufficient for resistance to hypoxia. By probing the 85 evolutionarily conserved hypoxia adaptation response (Pena, Sherman et al, 2016, Wang, Lim 86 et al, 2019, Wojtovich, Nadtochiy et al, 2012b, Wojtovich, Nadtochiy et al, 2013, we show that 87 tools like mtON allow precise determination of cause and effect in physiologic models. 88 89 RESULTS & DISCUSSION 90 Light-activated proton pump mitochondria-ON (mtON) is expressed in mitochondria.…”
mentioning
confidence: 77%
“…The targets of UPR mt signaling include glycolysis, chaperones, proteases, and antioxidants (6). Accordingly, we previously showed that UPR mt induction was protective against anoxiareoxygenation in C. elegans (17). Herein we hypothesized that induction of an ATF5-dependent UPR mt may be cardioprotective.…”
mentioning
confidence: 94%